RV to PA conduits: impact of transcatheter pulmonary valve replacement in adults – a national register study. (4th May 2017) - Skoglund, Kristofer; Svensson, Gunnar; Thilén, Ulf; Dellborg, Mikael; Eriksson, Peter
Abstract: Objective: The use of a conduit is an established surgical method for reconstruction of the right ventricular outflow tract in congenital heart disease; however, its limited durability makes reintervention almost inevitable. We studied the trends in new implantation, reoperation, and transcatheter pulmonary valve replacement (TPVR) from a Swedish national perspective. Design and results: The Swedish registry of congenital heart disease (SWEDCON) was used to collect data. From 2000–2014, there was an increase in adult patients with conduits from 122 to 536. There were 60 surgical conduit replacements, 40 TPVRs and 176 new conduit implantations in the study period. Perioperative mortality was <1%. The yearly number of new implantations and reoperations both doubled over the study period. Patients with new implantations were older (mean age, 36 years) compared with the reoperation and TPVR groups (mean age, 26 years) with the majority of patients having tetralogy of Fallot. The majority of conduit reinterventions were surgical also after the introduction of TPVR in 2007, with no significant difference regarding diagnosis, gender, age, or previous number or longevity of conduits. Conclusion: The number of adults with conduits increased steadily with most conduit-related operations being new implantations in patients with tetralogy of Fallot. Surgical conduit replacements increased significantly and represented the majority of conduit reinterventions after the introduction of TPVR, indicating that TPVR is not used for the majority of patients with conduit failure. Diagnosis, gender, age, or previous number or longevity of conduits had no impact on choosing surgical replacement vs. TPVR.